2005
DOI: 10.1055/s-2005-870596
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Myoepithelioma of the Rhinopharynx: Case Report

Abstract: Malignant myoepitheliomas are rare tumors of salivary glands. Most occur in the parotid gland; few other sites of origin are described. Malignant myoepithelioma of the rhinopharynx has only been reported twice. Because the lesion is so rare, there are no specific indications for its treatment. We present a third case of malignant myoepithelioma in the rhinopharynx and discuss its diagnostic and therapeutic aspects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Malignant transformation is usually seen in the long run in untreated tumors and recurrent benign tumors [6]. Although malignant myoepitheliomas are usually locally invasive and destructive, distant metastases are rare [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant transformation is usually seen in the long run in untreated tumors and recurrent benign tumors [6]. Although malignant myoepitheliomas are usually locally invasive and destructive, distant metastases are rare [11].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant myoepitheliomas are differentiated from benign myoepitheliomas according to their histopathologic features [2,11] The malignancy findings are infiltrative growth pattern, high mitotic rate, cellular pleomorphism, cytologic atypia, and necrotic areas [2,6]. Malignant transformation is usually seen in the long run in untreated tumors and recurrent benign tumors [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although most are biologically benign, malignant examples have been reported at a number of sites, including lacrimal gland, tongue base, masticator space, nasal cavity, maxillary sinus, nasopharynx, larynx, and vulva. 4,8,[11][12][13][20][21][22]29,30 With rare exceptions, such as the 1979 case report of ''intracranial cylindroma'' in the chiasmal region by Kasumova et al, 15 and a 1997 series of salivary gland tumors of the sellar region reported by Hampton et al, 9 myoepithelial/salivary gland lesions are not considered in the spectrum of intracranial neoplasms. Herein, we report a dura-based malignant myoepithelioma.…”
mentioning
confidence: 97%
“…Tüm tükrük bezi malignitelerinin %1'inden azýný oluþtururlar (1)(2)(3). Ýlk MM vakasý 1975'de Stromeyer ve arkadaþlarý tarafýndan sunulmuþtur.…”
unclassified
“…MM genellikle parotis bezinden kaynaklanýr, ancak oral kavite, çene, damak, larenks ve retromolar alan gibi minör tük-rük bezlerinin bulunduðu bölge-lerde de görülebilir (1,3). MM epitelyal kökenlidir ve pleomorfik adenom zemininden geliþebil-diði gibi kendiliðinden de geliþe-bilir (1,3,4). Pleomorfik adenomdan (PA) geliþen ve yumuþak damak orjinli MM ise çok daha nadir görülür.…”
unclassified